Investigating the beneficial traits of Trichoderma hamatum GD12 for sustainable agriculture—insights from genomics - Studholme, David J.; Harris, Beverley; Le Cocq, Kate; Winsbury, Rebecca; Perera, Venura; Ryder, Lauren; Beale, Michael; Ward, Jane; Thornton, Christopher R.; Grant, Murray (Frontiers in Plant Science, 2013)
Trichoderma hamatum strain GD12 is unique in that it can promote plant growth, activate biocontrol against pre- and post-emergence soil pathogens and can induce systemic resistance to foliar pathogens. This study extends previous work in lettuce to demonstrate that GD12 can confer beneficial agronomic traits to other plants, providing examples of plant growth promotion in the model dicot, Arabidopsis thaliana and induced foliar resistance to Magnaporthe oryzae in the model monocot rice. We further characterize the lettuce-T. hamatum interaction to show that bran extracts from GD12 and an N-acetyl-β-D-glucosamindase-deficient mutant differentially promote growth in a concentration dependent manner, and these differences correlate with differences in the small molecule secretome. We show that GD12 mycoparasitises a range of isolates of the pre-emergence soil pathogen Sclerotinia sclerotiorum and that this interaction induces a further increase in plant growth promotion above that conferred by GD12. To understand the genetic potential encoded by T. hamatum GD12 and to facilitate its use as a model beneficial organism to study plant growth promotion, induced systemic resistance and mycoparasitism we present de novo genome sequence data. We compare GD12 with other published Trichoderma genomes and show that T. hamatum GD12 contains unique genomic regions with the potential to encode novel bioactive metabolites that may contribute to GD12's agrochemically important traits.